LANDSCAPE, SPICES MANGOSTEEN TREE AND ITS CULTIVATION IN THE CONDITIONS OF UZBEKISTAN - Muhabbat Davlatova Urmanovna (Galaxy International Interdisciplinary Research Journal, 2021)
It produces fruits of mandarin size, which are called mangosteen, they are the best tasting fruits in the world in many circles. Young leaves are pink. The article is based on the cultivation of mangosteen in the Republic and the technology of its cultivation. These are not all the nutrients in mangosteen, but they have the highest concentration, so they can be considered specialized. And the useful ingredients already given are enough not only for your taste but also for the healing fruit.